Oxygen level is a critical regulator of human B cell differentiation and IgG class switch recombination - Koers, Jana; Marsman, Casper; Steuten, Juulke; Tol, Simon; Derksen, Ninotska I. L.; ten Brinke, Anja; van Ham, S. Marieke; Rispens, Theo (Frontiers in Immunology, 2022)
The generation of high-affinity antibodies requires an efficient germinal center (GC) response. As differentiating B cells cycle between GC dark and light zones they encounter different oxygen pressures (pO2). However, it is essentially unknown if and how variations in pO2 affect B cell differentiation, in particular for humans. Using optimized in vitro cultures together with in-depth assessment of B cell phenotype and signaling pathways, we show that oxygen is a critical regulator of human naive B cell differentiation and class switch recombination. Normoxia promotes differentiation into functional antibody secreting cells, while a population of CD27++ B cells was uniquely generated under hypoxia. Moreover, time-dependent transitions between hypoxic and normoxic pO2 during culture - reminiscent of in vivo GC cyclic re-entry - steer different human B cell differentiation trajectories and IgG class switch recombination. Taken together, we identified multiple mechanisms through which oxygen pressure governs human B cell differentiation.